The Muslim Mothers’ Understanding of Breastfeeding Command in the Quran: A Case Study in Yogyakarta - Astari, Rika; Bustam, Betty Mauli Rosa; Perawironegoro, Djamaludin (Fakultas Adab and Humaniora, Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
PurposeThis article aimed to explore the Muslim mothers' understanding of breastfeeding verses, the factors of the role of ulama, community organizations, and the impact of understanding verses on breastfeeding practices.MethodThe study was qualitative research employing a descriptive case study design. It involved Muslim preachers and mothers as the key informants in Yogyakarta. Intensive observation and interview were done to get the intended data. The collected data and information were qualitatively analyzed to unveil Muslim mothers’ understanding of breastfeeding in Islam.Results/findingsThe study' showed those who believed that the Quran obligated breastfeeding did it as an attempt to fulfill the obligations without understanding the benefits that come with it. This was a consequence of the absence of socialization of the breastfeeding-related Quranic verses' content.ConclusionThe study concluded that Muslim preachers had not reached Muslim mothers in Yogyakarta with breastfeeding verses.